Alterations in Helicobacter pylori Triggered by Contact with Gastric Epithelial Cells - Johnson, Elizabeth M.; Gaddy, Jennifer A.; Cover, Timothy L. (Frontiers in Cellular and Infection Microbiology, 2012)
Helicobacter pylori lives within the mucus layer of the human stomach, in close proximity to gastric epithelial cells. While a great deal is known about the effects of H. pylori on human cells and the specific bacterial products that mediate these effects, relatively little work has been done to investigate alterations in H. pylori that may be triggered by bacterial contact with human cells. In this review, we discuss the spectrum of changes in bacterial physiology and morphology that occur when H. pylori is in contact with gastric epithelial cells. Several studies have reported that cell contact causes alterations in H. pylori gene transcription. In addition, H. pylori contact with gastric epithelial cells promotes the formation of pilus-like structures at the bacteria–host cell interface. The formation of these structures requires multiple genes in the cag pathogenicity island, and these structures are proposed to have an important role in the type IV secretion system-dependent process through which CagA enters host cells. Finally, H. pylori contact with epithelial cells can promote bacterial replication and the formation of microcolonies, phenomena that are facilitated by the acquisition of iron and other nutrients from infected cells. In summary, the gastric epithelial cell surface represents an important niche for H. pylori, and upon entry into this niche, the bacteria alter their behavior in a manner that optimizes bacterial proliferation and persistent colonization of the host.